2018
DOI: 10.3389/fcimb.2018.00225
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Interleukin-1β Release by the Classical Swine Fever Virus Is Dependent on the NLRP3 Inflammasome, Which Affects Virus Growth in Monocytes

Abstract: Classical swine fever virus (CSFV) is a classic Flavivirus that causes the acute, febrile, and highly contagious disease known as classical swine fever (CSF). Inflammasomes are molecular platforms that trigger the maturation of proinflammatory cytokines to engage innate immune defenses that are induced upon cellular infection or stress. However, the relationship between the inflammasome and CSFV infection has not been thoroughly characterized. To understand the function of the inflammasome response to CSFV inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 57 publications
1
27
0
1
Order By: Relevance
“…Pyroptosis is another important biological process of the antiviral immune response. The activation of NLRP3 inflammasome-mediated pyroptosis during CSFV infection may help explain why CSFV establishes a persistent infection in leukocytes [34,97]. Generally, apoptosis, autophagy, and pyroptosis can be observed throughout the occurrence and development of CSFV, and they play key roles in ultimate decisions of CSFV-infected cells' fates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyroptosis is another important biological process of the antiviral immune response. The activation of NLRP3 inflammasome-mediated pyroptosis during CSFV infection may help explain why CSFV establishes a persistent infection in leukocytes [34,97]. Generally, apoptosis, autophagy, and pyroptosis can be observed throughout the occurrence and development of CSFV, and they play key roles in ultimate decisions of CSFV-infected cells' fates.…”
Section: Discussionmentioning
confidence: 99%
“…In viral infection, the assembly of the NLRP3 inflammasome is an important mechanism for caspase-1 activation, pyroptosis, and inflammation [26,88]. Studies by Fan et al showed that CSFV-infected porcine PBMCs caused the activation of an ATP-dependent K + ion channel and active NLRP3 inflammasome assembly, which led to caspase-1 activation and subsequent maturation and secretion of IL-1β, resulting in an inflammatory response [97]. Additional studies have showed that inhibiting the activation of the NLRP3 inflammasome can promote CSFV replication.…”
Section: Pyroptosis In the Pathogenesis Of Csfvmentioning
confidence: 99%
“…DNA viruses, such as poxvirus, herpes simplex virus, and adenovirus, can activate NLRP3 inflammasomes and promote IL-1β expression [19,20], while myxoma virus activates the NLRP3 inflammasome by inducing ROS and cathepsin B [21,22]. Many RNA viruses, such as infectious bronchitis virus, porcine reproductive and respiratory syndrome virus, and swine fever virus, induce IL-1β expression via the NLRP3 inflammasome [23][24][25]. The introduction of NLRP3 into ducks using a lentiviral expression system significantly increased the expression of NLRP3, IL-1β and IL-18 induced by E. coli and enhanced the degree of inflammation throughout the body [26].…”
Section: Introductionmentioning
confidence: 99%
“…Co-and post-translational processing of the polypeptide by cellular and viral proteases yields 12 cleavage products, including four structural proteins (C, Erns, E1, and E2) and eight nonstructural proteins (N pro ,p7,NS2,NS3,NS4A,NS4B,NS5A,and NS5B) (Heinz-Jurgen et al, 1991). CSFV can infect several cells types, including immune cells, leading to cellular immunosuppression (Fan et al, 2018). However, CSFV infection does not cause typical pathological changes, and the underlying infection mechanisms remain unclear (Bensaude, 2004;Johns et al, 2009).…”
Section: Introductionmentioning
confidence: 99%